FLUORINE AND TENSIDE CONTAINING FILM FORMING COATING AS A WAY TO SAVE THE LIGHT FRACTIONS OF THE HYDROCARBON COMPOUNDS IN THE TANKS - Spaska, O. A.; Ivanov, S. V. (Science and Transport Progress, 2008)
The composition and properties of fluorosurfactant protective coating against evaporation of light fractions of petrols during their long-term storage in reservoirs are analysed, the research of protective coating components interaction is conducted, and their IR-spectra are computed by a quantum-mechanical method using Hiperchem program package.